Efek Model Tumpangsari dan Pengaturan Barisan Jagung terhadap Evaluasi Keuntungan Hasil Jagung dan Kacang Nasi Kultivar Lokal Timor dalam Tumpangsari - Syprianus Ceunfin (Savana Cendana, 2018)
The decrease of agricultural products is currently one of the challenges for agricultural researchers because of the increasingly narrow farmland and highly not used land areas. The land productivity and crop production with utilize joined crops in some areas of both seasonal and long life crops as a solution. Cultivation of rice been is intercrop between maize crops. The objective of this research is to know the effect of intercropping models and the arrangement of maize cropping on the results and to evaluate the benefits of Timor cultivars and beans in intercropping system. All treatments of the plot experiment were arranged in a Factorial Randomized Completely Block Design 3×2+monoculture with three replicates Treatment, the first factor is intercropping model consisting of three levels: interspace intercropping; and Salome intercropping (Timor model); Alternative intercropping and the second factor is the arrangement of maize cropping spacing: Single row; Double row. The parameters observed were the weight of the maize seed per plot (t/ha), the weight of the rice beans per plot (t/ha), total LER, total ATER, crop aggressivity, Plant Competition Ratio. The data collected were analyzed using Factorial Randomized Block Design Anova and then continued with Duncan test at level α 0,05 using SAS 9.01 program. The results showed that there was an interaction of dry weight of maize kernels per plot, total LER, total ATER, and the ratio of maize competition. Intercropping yields ≥1, which is advantageous in the intercropping model treatment as well as on the arrangement of crop rows.